Asesmen Akhlak Mulia: Suatu Model Alternatif Penilaian Pembelajaran Agama - Siti Muri’ah (Universitas Islam Negeri Mataram, 2008)
One weakness of akhlak teaching method applied in schools is its teacher centered assessment. Teachers feel as the most well-informed sources about students’ akhlak while teachers’ capability of knowing students’ akhlak comprehensively is limited. Teachers’ chance to meet face-to-face with students is only in the learning process so that teachers’ assessment can not show the real akhlak of their students. Teachers should involve other parties who often associate with students, especially their peers. In addition, assessment instrument used by the teachers should not be limited to examination only. Therefore, comprehensive akhlak assessment is needed. In this writing, I describe alternative method to assess students’ akhlak. With this method, we can assess batiniyah dimensions including willingness, conscience, value and attitude and also lahiriyah dimensions manifested in behaviors. This method applies self and peer assessment by involving students in inter and intra relations. Assessment instruments could be questionnaires, observation and portfolios in likert scale, semantic differential and thurstone scale.